2012
DOI: 10.1063/1.3692388
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared isotopic study of ZnC3: Identification of the ν1(a′) mode

Abstract: An isomer of ZnC(3) with bent structure in its (1)A(') electronic state has been detected in the products from the dual laser ablation of carbon and zinc rods that were trapped in solid Ar at ~12 K. Measurements of (13)C isotopic shifts have enabled the identification of the ν(1)(a(')) asymmetric carbon stretching fundamental at 1858.9 cm(-1). The experimental results are in good agreement with the predictions of DFT-B3LYP/6-311G(d) calculations that indicate a singlet bent isomer ground state structure with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…On the other hand, in the case of magnesium tricarbide a theoretical study 36 predicts a rhombic ground state, with an open-chain isomer lying slightly higher in energy. Experimental and theoretical studies [37][38][39][40][41][42][43][44][45][46] have also been reported for first-row transition metal tricarbides, such as C 3 Sc, C 3 Ti, C 3 Cr, C 3 Mn, C 3 Fe, C 3 Co, C 3 Cu, and C 3 Zn.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the case of magnesium tricarbide a theoretical study 36 predicts a rhombic ground state, with an open-chain isomer lying slightly higher in energy. Experimental and theoretical studies [37][38][39][40][41][42][43][44][45][46] have also been reported for first-row transition metal tricarbides, such as C 3 Sc, C 3 Ti, C 3 Cr, C 3 Mn, C 3 Fe, C 3 Co, C 3 Cu, and C 3 Zn.…”
Section: Introductionmentioning
confidence: 99%